Enabling Autonomous Agents for Mobile Wireless Sensor Networks. - Castillo-Sánchez, José Borja; Cano-García, José Manuel; González-Parada, Eva; Frasheri, Mirgita (MDPI, 2025)
Wireless sensor networks (WSNs) play a pivotal role in monitoring and acting applications. However, suboptimal deployments and traffic imbalances lead to rapid network exhaustions. To address this, topology changes could be carried out by mobile robots. In this work, a software package to study different strategies and algorithms for the deployment, operation, and retrieval of mobile WSN is introduced. This package employs the globally known software ecosystem for robotics, ROS (Robot Operating System) 2, allowing to study the above-mentioned strategies and algorithms in simulation or in actual deployments. Two strategies concerning robot control are compared, the Social Potential Fields-only approach and an intelligent Agent layer. Each strategy is tested and optimized with different parameters. Results show that the Agents approach yields more consistent results and globally better metrics in terms of network lifetime and coverage.
Keywords: Redes informáticas; Redes de sensores inalámbricas; Métodos de simulación; Robots autónomos; mobile wireless sensor networks; ROS 2; Mobile robotos; Networking; Network simulation; Ad hoc networks